SISTEM PENDUKUNG KEPUTUSAN DETEKSI PENYAKIT KANKER PAYUDARA MENGGUNAKAN ALGORITMA NAIVE BAYES - Ivandari Ivandari; Erni Rahmawatie; M. Adib Al Karomi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Cancer is one of the biggest causes of death in the world. Data from the International Agency for Research of Cancer (IARC) states that in 2012 more than 8.2 million people died from cancer. From these data it is known that breast cancer is the most common type of cancer suffered by 19.2% of all cancer cases. The amount of data and records related to cancer patient cases can  be  useful  if  from  this  data  an  information  or  new  knowledge  can  be retrieved. Data mining is a field of knowledge that processes past data to be used as new information and knowledge. From the comparative research of data mining algorithms for detection of breast cancer in 2017 naive bayes is the best algorithm. Naive Bayes is proven to have a higher level of accuracy than other algorithms. In this study a decision support system for the detection of breast cancer was made. The system created using this Excel application can be one of the recommendations. The method used for calculation is the probability of naive bayes..Keywords: Naive bayes, Microsoft excell, decission support system